Mandatory audit firm rotation and auditor independence: empirical evidence from Nigerian listed banks. (1st January 2013) - Kighir, Apedzan Emmanuel
The consolidation of banking sector in Nigeria in 2006 brought about the introduction of mandatory audit firm rotation as part of banks code of corporate governance with the aim of further strengthening auditors independence. Internationally, the debate on the propriety of mandatory rotation of external auditors by companies assumed greater prominence following corporate failures across the globe especially the collapse of Enron and WorldCom in the USA and Parlmalat in Italy. The research employs cross sectional research design to gather panel data from mega money deposit banks in Nigeria using multivariate logistic regression as method of analysis. The research found that there is no significant relationship between audit firm rotation and auditor independence. This is inconsistent with prior work of DeFond et al. (2002), but consistent with the work of DeAngelo (1981). The research concludes that there is no statistically significant relationship between audit firm rotation and auditor independence.